2014
DOI: 10.1155/2014/245952
|View full text |Cite
|
Sign up to set email alerts
|

Discoscopic Findings of High Signal Intensity Zones on Magnetic Resonance Imaging of Lumbar Intervertebral Discs

Abstract: A 32-year-old man underwent radiofrequency thermal annuloplasty (TA) with percutaneous endoscopic discectomy (PED) under local anesthesia for chronic low back pain. His diagnosis was discogenic pain with a high signal intensity zone (HIZ) in the posterior corner of the L4-5 disc. Flexion pain was sporadic, and steroid injection was given twice for severe pain. After the third episode of strong pain, PED and TA were conducted. The discoscope was inserted into the posterior annulus and revealed a migrated white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…38 Nevertheless, the results in this study clearly indicate that this zone is related to the disc degeneration in Case 3, which could be a radiographic marker for disc degeneration. 3538 Although the nature of the HIZ is still not clear, we speculate that the HIZ might be related to the geometry of degenerated discs. More studies are needed in order to understand this phenomenon.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…38 Nevertheless, the results in this study clearly indicate that this zone is related to the disc degeneration in Case 3, which could be a radiographic marker for disc degeneration. 3538 Although the nature of the HIZ is still not clear, we speculate that the HIZ might be related to the geometry of degenerated discs. More studies are needed in order to understand this phenomenon.…”
Section: Discussionmentioning
confidence: 91%
“…31 In addition, the higher water content zone predicted in Case 3 (shown in Figure 7D) is consistent with the High Intensity Zone (HIZ) seen in T2-weighted MRI images. 3538 The HIZ was initially proposed as a marker to diagnose low back pain, 37,39 whereas it was also found in asymptomatic subjects later. 38 Nevertheless, the results in this study clearly indicate that this zone is related to the disc degeneration in Case 3, which could be a radiographic marker for disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histograms of non-degenerated IVDs based on T2W-images or T2-maps data should display two well separated peaks, one from AF and one from NP. In the process of IVD degeneration, an increased number of AF fissures are developed that may result in leakage of NP into the AF [20,21]. Hypothetically, such leakage could be characterized by a region of high signal intensity in the otherwise low signal AF.…”
Section: Discussionmentioning
confidence: 99%
“…Because migration of fibroblasts and other cells is important for wound healing and AF tissues undergo tears, fissures, and fractures, one function of AF cells may be to respond to damaged areas by migrating toward the wound and initiating the healing process. One area the AF cells may migrate to are high-intensity zones—the areas of AF tissues that are bright on magnetic resonance imaging scan, which represent tears, granulated tissue, and inflammation [28,29]. It has been reported that high-intensity zones contain small round cells and fibroblasts, yet the origins of these cells have not been studied.…”
Section: Discussionmentioning
confidence: 99%